Using Transformations to Predict and Smooth Time Series - et. al., Jassim N Hussain, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Time series has a leading position in statistical Analysis. Nowadays, many economic and industrial operations have been built based on time series. These operations include predicting the product demand variation, the future product prices oscillation, the stock storing control etc. This paper presents a study to show the effect of transformation and smoothing on the performance of the time series. The research results have shown a significant improvement in time-series operation can be noticed when the principles of transformation and smoothing are applied on time series.